The Limits of the Commune: A Review of The Mystery of the Kibbutz - Nye, John V. C. (Journal of Economic Literature, 2020)
Ran Abramitzky's book, The Mystery of the Kibbutz: Egalitarian Principles in a Capitalist World, tries to answer the questions of why the communal kibbutz worked so well in Israel's formative years and what limits its current success in modern Israel. Initial ideological commitment and the special circumstances of Israel's founding led to unusual success when combined with well-thought-out rules on behavior and entry. Over time, the commitment to socialistic income sharing has not worked so well, given modern technology and global commerce. The author links up these ideas to the broader issue of organizational structure but misses out on some opportunities to test the ideas further. (JEL D31, D63, D82, J24, P13, Q13)